The role of women in japanese society - Nurseitova, L. D. (Journal of Oriental Studies, 2016)
The women role in modern Japanese society, carried out in a conditions of traditional and cultural globalization. Female factor persistently breaks into the modern world view. The role of Japanese women is a major challenge in terms of the dynamics of socioeconomic and political development of Japanese society in the XXI century. This article discusses the changes and developments of the role of women in modern Japanese society.